2016
DOI: 10.1128/jvi.01220-16
|View full text |Cite
|
Sign up to set email alerts
|

Canonical and Variant Forms of Histone H3 Are Deposited onto the Human Cytomegalovirus Genome during Lytic and Latent Infections

Abstract: Chromatin is the nucleoprotein complex that protects and compacts eukaryotic genomes. It is responsible for a large part of the epigenetic control of transcription. The genomes of DNA viruses such as human cytomegalovirus (HCMV) are devoid of histones within virions but are chromatinized and epigenetically regulated following delivery to the host cell nucleus. How chromatin is initially assembled on viral genomes and which variant forms of the core histone proteins are deposited are incompletely understood. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 84 publications
1
34
0
Order By: Relevance
“…(iv) The association with chromatin is dynamic. Specifically, it has been demonstrated that the MIEP is associated with transcriptionally repressive chromatin in latently infected cells but, in cells that support reactivation, the histones at the MIEP are acetylated consistent with the transcriptional activity observed [10,[18][19][20]. (v) Inflammation (and the associated signaling activity) promotes HCMV reactivation in multiple models of HCMV latency [7,11,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 76%
“…(iv) The association with chromatin is dynamic. Specifically, it has been demonstrated that the MIEP is associated with transcriptionally repressive chromatin in latently infected cells but, in cells that support reactivation, the histones at the MIEP are acetylated consistent with the transcriptional activity observed [10,[18][19][20]. (v) Inflammation (and the associated signaling activity) promotes HCMV reactivation in multiple models of HCMV latency [7,11,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 76%
“…PML protein is thought to associate with transcription factors, such as STAT1 and IRF3, which are involved in regulating IFN and IFN-stimulated gene (ISG) expression (Chen et al, 2015). Furthermore, PML NBassociated transcriptional repressors, such as Sp100 and DAXX, have been shown to restrict viral gene expression in HSV-1, ADV, HPV, Epstein Barr Virus (EBV), and HCMV infection (Negorev et al, 2006;Kim et al, 2011;Schreiner et al, 2013;Stepp et al, 2013;Tsai et al, 2014;Albright and Kalejta, 2016).…”
Section: Viruses Interact With Pml Nbs To Establish Infectionmentioning
confidence: 99%
“…The histone loader Histone Regulatory Homologue A (HIRA) interacts with ASF1a and preferentially loads histone H3.3/H4 complexes onto DNA in a replication-independent manner throughout the cell cycle, for example at areas of active transcription (17, 46). HIRA regulates the alpha-herpesvirus herpes simplex virus and the beta-herpesvirus cytomegalovirus latency (4750). HIRA is also implicated in maintenance of HIV latency (51), but to our knowledge has not been investigated in the regulation of gamma-herpesvirus latency.…”
Section: Resultsmentioning
confidence: 99%
“…Histones 3.1 and 3.3 are loaded onto the beta-herpesvirus cytomegalovirus genomes (50), and intriguingly, their deposition did not require transcription or replication of the viral genome. This finding raises the possibility that conserved mechanisms may load histones onto herpesvirus genomes more broadly.…”
Section: Discussionmentioning
confidence: 99%